RESISTENSI DAN RESPON ETNIK AFRO-AMERIKA ATAS MARJINALISASI ETNIK ANGLO-AMERIKA DALAM PUISI-PUISI KARYA HUGHES - Iswalono, Sugi (LITERA, 2014)
This study aims to describe the forms of and responses to racial hegemony and the Afro-American ethnic group's self-identity in Hughes's poems. It employed the qualitative descriptive approach. The data sources were Hughes's poems entitled "I, Too, Sing America", "Let America be America Again", and "Theme for English B". The data were analyzed by means of the postcolonialism theory, enriched by historical, socio-cultural, and political information during the post-civil-war era till 1960s in the United States of America. The findings are as follows. First, racial hegemony appears in the form of the negative stereotype of the Afro-American ethnic group. The negative stereotype leads to the marginalization of the Afro-American ethnic group, reflected by the injustice and tyranny by the majority ethnic group. Second, responses to racial hegemony are manifested in the Afro-American ethnic group's awareness of dignity, self-esteem, and self-confidence as foundations to demand equality and to show their existence amid the white people ethnic group's domination. Third, the pride of ethnic identity is actually a potential to realize Amerian ideals as a nation highly respecting equality and diversity as aspired by the founding fathers.